Time-domain spectral finite element method for analysis of torsional guided waves scattering and mode conversion by cracks in pipes. (1st August 2019) - Yeung, Carman; Ng, Ching Tai
Highlights: A time-domain spectral finite element is used to simulate torsional waves in pipes. A crack model is proposed to simulate the wave scattering and mode conversion effect. A parametric study using 3D finite element is used to gain physical insights. Experiments are conducted to verify the time-domain spectral finite element method. Abstract: This paper presents a computationally efficient time-domain spectral finite element method (SFEM) and a crack model to take into account guided wave propagation, scattering and mode conversion in pipes. The proposed SFEM couples torsional and flexural motions of guided waves. A cracked element is proposed to predict the scattering and mode conversion effect of guided wave interaction with the crack in the pipes. The proposed SFEM and cracked element are verified by 3D finite element and experimental data. The results show that the proposed SFEM is able to predict the torsional guided wave propagation, scattering and mode conversion accurately. A series of numerical and experimental case studies are carried out to investigate the effect of the crack size on the scattering and mode converted guided waves. The findings of the study provide physical insights into the guided wave scattering and mode conversion and further advance the development of damage detection using guided waves.